Burning of Fountain Candles Indoor—A Moment of Joy versus Indoor Air Quality Concerns - Agnese Araja; Maja Remskar; Maris Bertins; Laima Plaveniece; Arturs Viksna (Proceedings)
Burning candles, magic candles, incense, and pyrotechnics such as fountain candles creates a sense of joy and celebration in various life and social events [...]